Integrasi Kasir Pintar Untuk Peningkatan Daya Saing UMKM Warung Kuliner Dhoho Plaza Kota Kediri - Jaza', Mochammad Miftakh; Khoiruddin, M Ilman; Pinasty, Rekananta Nasa; Barira, Imelda Nurrahmatul; Adhitya, Toni (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Candaria is an MSME that utilizes the potential of pineapple fruit, typical of Kediri Regency, to produce processed products with added value. However, Candaria's branding and product promotion strategies are still limited to the simple use of social media. This community service activity aims to assist Candaria in strengthening branding and increasing product promotion through social media, especially Instagram. The method used is the Asset- Community Development approach, which utilizes local assets such as superior products and available technology to optimize the potential of MSMEs. Assistance is carried out by creating creative video content containing product introductions and education about processed pineapple typical of Kediri. The results of the activity show an increase in the quality of Candaria's digital content, which has an impact on increasing product visibility on social media and consumer appeal. Through this activity, Candaria is able to develop a more effective and sustainable marketing strategy.